Optimizing the Management of Public Funds at Islamic Banks Through Liability Management - Fhika Noverita; Anasari Anasari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the strategic frameworks governing asset liability management within Islamic banking institutions to optimize public fund management without violating religious jurisprudence. Utilizing a qualitative library research design, the analysis evaluates secondary data spanning statutory regulatory frameworks, central bank macrofinancial records, and authoritative financial treatises. The findings reveal that effective liability management depends on a systematic partitioning between custody based accounts and investment partnerships to mitigate unexpected funding mismatches and control operational costs. Furthermore, integrating diversified capital pools from sovereign entities, educational centers, and social finance foundations provides a durable liquidity buffer that enhances institutional resilience against macroeconomic contractions. The study demonstrates that long term stability requires a balanced configuration that harmonizes profit sharing expectations with strict regulatory parameters. Ultimately, the successful mobilization of public liquidity is achieved by combining robust technological platforms, digital transaction convenience, and dual corporate governance oversight, which collectively reinforce institutional trust and secure sustainable economic growth in accordance with Islamic ethical standards.